Flattening the COVID-19 Curve: The Impact of Contact Restrictions on the Infection Curve in Germany - Valentowitsch, Johann (Das Gesundheitswesen, 2020)
Although Germany is coping well with the coronavirus crisis, many voices are currently being raised that fundamentally question the success of the contact restriction strategy to contain the virus. I show in this study that there is no justification for such criticism. In fact, contact restrictions have flattened the infection curve and were possibly decisive for the good German performance in the crisis.Obwohl Deutschland mit der Coronavirus-Krise gut zurechtkommt, werden derzeit viele Stimmen laut, die den Erfolg der Kontaktbeschränkungsstrategie zur Eindämmung des Virus grundlegend in Frage stellen. Ich zeige in dieser Studie, dass es keine Rechtfertigung für eine solche Kritik gibt. Die Einschränkung sozialer Kontakte hat tatsächlich einen wesentlichen Beitrag zur Abflachung der Infektionskurve geleistet und war damit maßgebend für das gute deutsche Krisenmanagement.
Keywords: COVID-19; Coronavirus; Contact Restrictions